A silver river in a silver world Dutch Trade in the Río de la Plata,1648–1678 - Freeman, David ca. 20./21. Jh (Cambridge University Press, 2020)
Drawing on a wide and rich array of sources, this book explores the nature and extent of Dutch trade and commerce in the Río de la Plata during three decades of the least-studied century (1650-1750) of Spain's rule in the Americas. In doing so, it raises important questions about trade in colonial South America and how it was impacted by the Dutch, suggesting that these transactions were carried out within the confines of the law, contradicting common beliefs among scholars that this trading was not regulated. The book contributes to a growing literature on contraband trade, administration, networks, and corruption while challenging narratives of exclusively Spanish influence on the Americas
Keywords: Geschichte 1648-1678; Silver industry -- Río de la Plata Region (Argentina and Uruguay) -- History -- 17th century; Silberhandel; Überseehandel; Kaufmann; Netherlands -- Commerce -- History -- 17th century; Río de la Plata Region (Argentina and Uruguay) -- Commerce -- History -- 17th century; Río de la Plata Region (Argentina and Uruguay) -- Commerce -- Netherlands; Netherlands -- Commerce -- Río de la Plata Region (Argentina and Uruguay); Niederlande; Buenos Aires; Río-de-la-Plata-Gebiet